Comparative performance of improved meat goats in Malya, Tanzania - Das, S.M.; Sendalo, D.S.C. (1992)
Records on liveweight, growth and reproductive performance of Blended (BLD), Blended x Galla (BG) and Kamorai x indigenous (KI) goats for a period of over 10 years (1970-1980) in Malya, Tanzania were analysed. For BLD, BG and KI goat kids, birth weight and live weight averages were determined. Sex and birth type had significant effects on all live weight measures while year of birth did not. Mean litter size for six parities for BLD, BG and KI does were examined. It was recommended that BLD goats with higher live weights and efficient reproductive performance compared to BG and KI goats should be used for crossbreeding purposes to improve the meat production from goats in the rural areas.